Reduced Soil Gross N2O Emission Driven by Substrates Rather Than Denitrification Gene Abundance in Cropland Agroforestry and Monoculture. Issue 3 (7th March 2022) - Luo, Jie; Beule, Lukas; Shao, Guodong; Veldkamp, Edzo; Corre, Marife D.
Abstract: Conversion of monoculture to agroforestry (integrating trees with crops) is promoted as a promising management in reducing N2 O emissions from croplands. How agroforestry influences gross N2 O emission (N2 O + N2 from N2 O reduction) and uptake (N2 O reduced to N2 ) compared to monoculture is unknown. We used the 15 N2 O pool dilution technique to quantify these processes using soil cores (top 5 cm) incubated in the field with monthly measurements over two growing seasons (2018–2019) at two sites (each with paired agroforestry and monoculture) and one site with monoculture only. The unfertilized tree rows showed the lowest gross N2 O emissions ( P  ≤ 0.002). Although tree rows occupied only 20% in agroforestry, gross N2 O emissions tended to decrease by 6–36% in agroforestry (0.98–1.02 kg N2 O‐N ha −1  yr −1 ) compared to monoculture (1.04–1.59 kg N2 O‐N ha −1  yr −1 ). Gross N2 O emissions were influenced by soil mineral N, soil respiration, and moisture content rather than by denitrification gene abundance. Soil gross N2 O uptake was highest in the tree row and decreased with distance into crop rows ( P  = 0.012). The agroforestry tended to increase gross N2 O uptake by 27–42% (0.38–0.44 kg N2 O‐N ha −1  yr −1 ) compared to monoculture (0.30–0.31 kg N2 O‐N ha −1  yr −1 ). In tree rows, soil gross N2 O uptake correlated with nirK gene abundance which was indirectly influenced by the low mineral N‐to‐soil CO2 ‐C ratio. Adjusting the tree and crop areal coverages of agroforestry and optimizing fertilization can further augment the benefits of agroforestry in reducing emission and increasing uptake of N2 O in soils. Plain Language Summary: Nitrous oxide (N2 O) is a potent greenhouse gas and its largest anthropogenic source is from nitrogen fertilization in agriculture. Conversion of cropland monoculture to agroforestry (integrating trees with crops) is one promising mitigation practice to reduce soil N2 O emissions from agriculture. We quantified gross rates of N2 O emission (N2 O + N2 from N2 O reduction) and uptake (N2 O reduced to N2 ) in the soil to evaluate how agroforestry performs compared to monoculture. Our findings showed that agroforestry decreased gross N2 O emissions and increased gross N2 O uptake. These were due to the absence of nitrogen fertilization and increased soil respiration (which partly indicated increase in carbon availability to soil microbes) in the tree row. These findings suggest that if fertilizer inputs are optimized without sacrificing crop yield or profit, combined with the impact of tree rows on increasing soil N2 O uptake, agroforestry will be an efficient mitigation strategy to curb N2 O emissions from croplands. The benefits of agroforestry in reducing gross N2 O emission and increasing gross N2 O uptake in soils should be included in the economic valuation to support its policy implementation and adoption by farmers. Key Points: The tree row in the agroforestry decreased annual gross N2 O emission and increased annual gross N2 O uptake compared to monoculture Reduced gross N2 O emission was directly regulated by mineral N, C availability, and WFPS rather than denitrification gene abundance The increased gross N2 O uptake in the agroforestry was largely controlled by the low mineral N‐to‐CO2 ‐C ratio in the tree row